THE STABILITY ANALYSIS OF OPTIMAL PLANS OF RETURNING SPENT WAGONS WITH VARIATIONS OF DAILY FIGURES - Skalozub, V. V.; Foksha, K. S. (Science and Transport Progress, 2008)
The problem of stability of optimum plans of empty cars return is investigated in the article. For stochastic planning model, using the statistic test method the values of plans sensitiveness to changes of input data are obtained.